ANALISIS KESALAHAN MENYELESAIKAN SOAL CERITA OPERASI BILANGAN BULAT MENGGUNAKAN PROSEDUR NEWMAN PADA SISWA SMP - Irsandi Kusuma; Dede Suratman; Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research generally is to describe the types of errors and find out the factors that cause students' error in solving mathematical story questions in the Integer operation learning material based on Newman's procedures. The subjects of this research were students of class VII A of SMP KRISTEN IMMANUEL II KUBU RAYA  and the research focus was on students' error in solving integer mathematical story questions by using  Newman's procedures. The results of data analysis showing that the type of error that mostly done by students is the process skill error. Students could not complete the solving steps correctly. Therefore, the students wrong in answering the mathematical story problem because the final answer depends on the solving process.Keywords: Math Story Problems, Newman's Procedures, Student Error